Effect of ferric ion [Fe3+] and [Fe2+] on SO2 adsorption ability of γ-Fe2O3 nanoparticles for mass-type gas sensors - Nguyen Thanh Vinh (Sensors and Actuators A: Physical, 2021)
The sensing material plays a very important role in determining the sensing properties of a gas sensor. In order to synthesise the sensing material, the precursors have a large effect on the properties of the sensing material. In this study, three types of γ-Fe2O3 nanoparticles were prepared with different ferric ion concentrations of [Fe3+] and [Fe2+] as precursors, by a typical facile chemical precipitation process and a following annealing treatment. A mass-type gas sensor was fabricated by using a quartz crystal microbalance (QCM) coated with various γ-Fe2O3 nanoparticles. The morphology, crystallisation, and gas adsorption characteristics of the γ-Fe2O3 nanoparticles were investigated. The effect of ferric ion concentrations of [Fe3+] and [Fe2+] on sensing properties is discussed in detail. Interestingly, the sensor based on γ-Fe2O3 nanoparticles synthesised with ferric ion [Fe3+] showed excellent sensing properties for the detection of SO2 gas, with high sensitivity and repeatability at room temperature. The experimental results clearly demonstrate that the γ-Fe2O3 nanoparticle is an excellent sensing material which may be suitable for practical sensing applications.